Toward a novel module for computerizing Quran’s full-script writing - Abudena, Mussa; Hameed, Shihab A. (International Journal of Computer System, 2015)
Arabic script is used by a multitude of languages and it is the second most widely used script in the world. Quran is revealed and written in Arabic but writing Quran scripts requires additional Arabic fonts that should reflect the recitation rules. Reciting Quran is mainly based on ten correct readings (Qira'at). There are two famous readings of Quran: qira'a of 'Asim ) )عاصن in the narration (riwayat) of Hafs )حفص( , that were widely used over the Islamic world, and secondly the qira'a of Nafi' ) اًفع( in the narration of Warsh )ورش( and the narration of Qaloon )قالوى( that is mainly used by Muslims in north Africa. Till today, The writing of Quran script is done manually by calligraphers using the traditional techniques (papers and pens). This takes long time (2-3 years) and huge effort as well as the high rate of errors. After getting the final hand written version then a digital processed (scanning, adding decoration, etc.) have to taking place to finalize Quran in its last version. This research tries to make use of digital technology to facilitate and computerize writing of Quran script and overcome the current weaknesses. Paper shows the initial proposed module and preliminary results obtained.